Gamma‐CaSO4 With Abnormally High Stability From a Hyperarid Region on Earth and From Mars. Issue 3 (18th March 2022) - Shi, Erbin; Wang, Alian; Li, Huafang; Ogliore, Ryan; Ling, Zongcheng
Abstract: Ordinary γ‐CaSO4 is a metastable calcium sulfate, while γ‐CaSO4 from the hyperarid region on Earth and from Mars has been found with abnormally high stability. In this study, we used multiple microanalyses to characterize the chemical and structural properties of two such γ‐CaSO4 : one from Atacama soil (#10‐d30) and the other from Martian meteorite MIL03346, 168. Silicon was determined to be quasi‐homogeneously distributed in Atacama γ‐CaSO4, while both silicon and phosphorus were detected in Martian γ‐CaSO4 . We found the abnormally high stability of those γ‐CaSO4 from hyperarid environments was due to the chemical impurities which filled their structural tunnels and blocked the entrance of atmospheric H2 O, with non‐detectable structural distortion. We propose that the γ‐CaSO4 with Si or Si and P impurities could have igneous origin or evaporative origin. Due to the extreme similarity in the structures of bassanite and γ‐CaSO4, their XRD patterns are almost non‐distinguishable; thus some martian "bassanite" minerals identified by Curiosity's CheMin instrument at Gale crater can actually be γ‐CaSO4 . The structural tunnels in γ‐CaSO4 would allow ions and ionic groups to fill, thus providing meaningful insights about the geological and geochemical processes experienced by it during the formation and transformation. The Raman spectrometer carried by the Perseverance and by ExoMars rovers will help the selection of samples enriched in γ‐CaSO4 at Jezero Crater and Oxia Planum, which should be sampled for in‐depth analysis on Mars and back to Earth. Plain Language Summary: In the laboratory, ordinary γ‐CaSO4 would adsorb atmospheric H2 O in minutes and transform to bassanite. However, the γ‐CaSO4 from the hyperarid region on Earth and from Mars has been found maintaining abnormally high stability for years. We used multiple microanalyses to characterize the chemical and structural properties of γ‐CaSO4 from Atacama soil and Martian meteorite MIL03346, 168. We found that silicon is quasi‐homogeneously distributed in Atacama γ‐CaSO4, while both silicon and phosphorus were determined in Martian γ‐CaSO4 . Our study demonstrated that abnormally high stability of γ‐CaSO4 was due to chemical impurities, which filled the structural tunnels that blocked the entrance of atmospheric H2 O. Due to extreme similarity in the structures of bassanite and γ‐CaSO4, their XRD patterns are almost non‐distinguishable. We anticipate that some "bassanite" identified by Curiosity's CheMin instrument at Gale crater could actually be γ‐CaSO4 . Our study shows that the structural tunnels in γ‐CaSO4 could be readily filled by ions and ionic groups, and even organic molecules as demonstrated by other studies. The Raman spectrometer carried by the Perseverance and ExoMars rovers would help the selection of samples enriched in γ‐CaSO4, for in‐depth analyses on Mars and return to Earth. Key Points: High stability of γ‐CaSO4 from hyperarid areas was found due to chemical impurities that filled tunnels and blocked entrance of H2 O The impure γ‐CaSO4 could have igneous and evaporative origins, significant for understanding geochemical process Some "bassanite" minerals identified by the CheMin instrument on Mars can actually be γ‐CaSO4